Impact of diabetes on three-year outcome after coronary stenting in patients with polyvascular atherosclerotic disease – a secondary analysis of the randomized TWENTE trials - Daphne van Vliet; Tineke H. Pinxterhuis; Eline H. Ploumen; Marlies M. Kok; Rosaly A. Buiten; Paolo Zocca; Ariel Roguin; Carl E. Schotborgh; Rutger L. Anthonio; Peter W. Danse; Edouard Benit; Adel Aminian; et al. (International Journal of Cardiology: Heart & Vasculature)
Background: The presence of polyvascular atherosclerotic disease is associated with a high-risk of adverse events following percutaneous coronary intervention (PCI). As the extent to which the presence of diabetes further increases this elevated risk is unclear, based on current literature, we sought to assess the long-term outcome after PCI in patients with polyvascular disease, comparing those with and without diabetes. Methods: The current study population consists of patients with known polyvascular disease, identified from a pooled patient-level database of 4 PCI trials in all-comers treated with new-generation drug-eluting stents; no exclusion criteria were set. The main composite endpoint was major adverse cardiac event (MACE: any myocardial infarction, emergent coronary bypass surgery, clinically indicated target lesion revascularization, or all-cause mortality). Results: 695 patients had polyvascular disease of whom 208(29.9 %) had diabetes. Patients with diabetes were older, had a higher body-mass-index, and had a higher prevalence of hypertension than those without diabetes. At 3-year follow-up, the incidence of MACE was significantly higher in polyvascular disease patients with diabetes (24.6 % vs.16.4 %, adj.HR:1.49, 95 %CI:1.05–2.12, p = 0.03), in particular insulin-treated patients, and was primarily attributable to a disparity in all-cause mortality which was more than twice as high in patients with diabetes (15.4 % vs.7.2 %, p < 0.001). Furthermore, the risk of repeated target vessel revascularization was higher in patients with diabetes (12.0 % vs7.0 %, adj.HR:1.88, 95 %CI:1.12–3.16, p = 0.02). Conclusions: In the high-risk population of PCI patients with polyvascular disease, the presence of diabetes represents a profoundly significant additional risk factor at long-term follow-up, associated with significantly higher adverse event risks.Trial registration: ClinicalTrials.gov NCT01066650 NCT0133170 NCT01674803 NCT02508714.